Relevancia de la comunicación ‘no verbal’ en el aula de ILE: ¿cómo hablan las manos en una lengua extranjera? - Lizasoain, Andrea; Walper, Katherina; Ortiz de Zárate, Amalia; Sepúlveda, Jazmín; Catripan, Evelyn (Colombian Applied Linguistics Journal, 2021)
This paper explores the use of hand gestures by three English as a Foreign language pre-service teachers and its relationship with their communicative competence. By means of multimodal analysis, the most common manual gestures are classified following Kendon’s continuum. Data was recorded in teaching simulations in which novice teachers adapted, carried out and tested activities to teach literature and foster language skills with their peers. Interviews with the participants further complement the data in order to examine their perceptions about their own bodily behaviour in this classroom setting. Results show that the nature of the gestures used is closely related to their communicative competence, and that they are not aware of the resources they select to communicate with the students and to give them instructions. This evidences the relevance of including embodied practices in teacher training.